The role of children in the transmission of SARS-CoV-2: review of the evidence and analysis of the trend of infection in the pediatric population - Khayamian, Yasmin; Casula, Laura; Minerba, Luigi; Massidda, Maria Valeria; Melis, Paola (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2022)
Background: The epidemiological knowledge about the diffusion and diffusibility of SARS-CoV-2 in the pediatric population is constantly updated and revised, but not always based on sound and thorough body of evidence. This study examines the trend of the virus in the pediatric population in the Italian context. Specifically, it investigates the evidence available about the role of the pediatric population in the transmission of SARS-CoV-2. Methods: Analysis of the incidence of SARS-CoV-2 in Italy in the age group ≤ 19 years and comparison with other countries. Systematic reviews and meta-analysis available on PubMed regarding the infection rate of the pediatric population were analyzed. Results: In the period between July 2020 and November 2020, the new cases in the pediatric population show an exponential increase, revealing a rapid growth of new infections. In the literature there is a large amount of studies about the spread and transmission of SARS-CoV-2 in the pediatric population, but only few quantitative synthesis are available. The lack of data about the secondary attack rate of a pediatric index case in primary studies combined with the frequent lack of good methods makes it difficult to determine the infection rate in children. The analyzed literature shows that: a) the majority of pediatric cases comes from family transmission; b) the index case in the clusters is predominantly adults; c) pediatric index cases appear to be responsible for a lower secondary attack rate compared to adult index cases. Conclusion: We observed an exponential increase of SARS-CoV-2 cases in the age group between 0 and 19 years between July 2020 and November 2020 in Italy, but the international literature indicates that children do not transmit SARS-CoV-2 more than adults. However, the evidence is not sufficient to draw firm conclusions.